Long noncoding RNA HULC accelerates liver cancer by inhibiting PTEN via autophagy cooperation to miR15a - Xiaoru Xin; Mengying Wu; Qiuyu Meng; Chen Wang; Yanan Lu; Yuxin Yang; Xiaonan Li; Qidi Zheng; Hu Pu; Xin Gui; Tianming Li; Jiao Li; et al. (Molecular Cancer, 2018)
Abstract Background Long noncoding RNA HULC is highly up-regulation in human hepatocellular carcinoma (HCC). However, the functions of HULC in hepatocarcinogenesis remains unclear. Methods RT-PCR, Western blotting, Chromatin immunoprecipitation (CHIP) assay, RNA Immunoprecipitation (RIP) and tumorignesis test in vitro and in vivo were performed. Results HULC is negatively associated with expression of PTEN or miR15a in patients of human liver cancer. Moreover, HULC accelerates malignant progression of liver cancer cells in vitro and in vivo. Mechanistically, HULC increasesthe expression of P62 via decreasing mature miR15a. On the other hand, excessive HULC increases the expression of LC3 on the level of transcription and then activates LC3 through Sirt1 (a deacetylase). Notably, HULC enhanced the interplay between LC3 and ATG3. Furthermore, HULC also increases the expression of becline-1(autophagy related gene). Therefore, HULC increases the cellular autophagy by increasing LC3II dependent on Sirt1.Noteworthy, excessive HULC reduces the expression of PTEN, β-catenin and enhances the expression of SAPK/JUNK, PKM2, CDK2, NOTCH1, C-Jun in liver cancer cells. Of significance, our observations also revealed that HULC inhibited PTEN through ubiquitin–proteasome system mediated by autophagy-P62.Ultimately,HULC activates AKT-PI3K-mTOR pathway through inhibiting PTEN in human liver cancer cells. Conclusions This study elucidates a novel mechanism that lncRNA HULC produces a vital function during hepatocarcinogenesis.